Developing the Indonesian Qualifications Framework's descriptors for Electrical Engineering as the basis of the Recognition of Prior Learning (RPL). (December 2018) - Zamtinah,; Supriyadi, E
Abstract: This study aims to: 1) describe the mechanism of the level 2 IQF (the Indonesian Qualifications Framework) descriptor development for electrical engineering, and 2) formulate a set of detailed-level-2 descriptors for electrical engineering. The method used to develop the descriptors is brainstorming between the researcher and several experts from both academicians and practitioners. Meanwhile, the method to formulate the IQF descriptors for electrical engineering is literature review referring to The Indonesian National Work Competency Standard ( SKKNI ) and focus group discussion involving experts from academicians, Professional Certification Institute Gema PDKB, the Association of Indonesian Electrical Works ( APEI ), Consortium for Electrical Installation Safety ( KONSUIL ), and industry practitioners such as PT. LEN Bandung, PT. Bukaka Teknik Utama, PT. Schneider Electric Indonesia, and PT. Smart Energi Semesta. The descriptors are in the form of the guttman scale questionnaire. The questionnaire was then tested on limited-scale respondents. The KR 20 method was employed to examine the reliability and resulted in r11 = 0.9; thus, the guttman scale questionnaire was considered "very reliable". The respondents consisted of 8 academicians, 8 electrical engineering teachers at vocational high schools, and 8 industrial practitioners. The collected data were then analyzed descriptively. This study resulted in a set of level 2 IQF descriptors which were designed according to the taxonomy of electricity system, namely electric power transmission system descriptors, electric power distribution system descriptors, and electric power utilization descriptors. In regard to electric power transmission system, 103 out of 154 (67%) descriptors were approved by more than 80% of respondents; for electric power distribution system, 83 descriptors (75%) were approved by more than 80% of respondents; and for electric power utilization system, 61 descriptors (94%) were approved by more than 80% of respondents